MEMBANGUN SEMANGAT MISIONER DAN SOLIDARITAS KRISTIANI MELALUI KOMUNITAS BASIS GEREJANI DI PAROKI MATER DEI MADIUN - Anastasia -; Wibowo Singgih (Lembaga Penelitian STKIP Widya Yuwana, 2019)
Globalization can make whosoever so focused with them and ignore the people's life around them. To overcome the individualistic attitude of the people of the Church, it needs to reemphasizes the importance of the Basic Ecclesial Communities among the people of the Churh. The Basic Ecclesial Community is a unit of Christians relatively small and easily gathered periodically to hear the word of God, a variety of daily problems, whether personal issues, groups or social problems, and finding solutions in the light of the Holy Scripture. This scientific work uses a qualitative research method which directed to answer the following research questions: What is the meaning of missionary works in the life of Catholics? What is the meaning of Christian solidarity? What is the understanding of the Basic Ecclesial Community and your involvement in it? The result of the research generally revealed that respondents understand the meaning and the missionary task, the comprehension and the format of solidarity, the meaning and the task of the Basic Ecclesial Community. But in fact, 8 (80%) of the respondents recognize that they never again carry out the Basic Ecclesial Community. Even though the respondents recognize that the Basic Ecclesial Community can make the missionary work and the solidarity develops towards the fellows with the same faith or the others. Therefore the Basic Ecclesial Community activity is very important because there people can live harmoniously, peacefully, friendly, helping one to another and become a place of the development of Jesus' evangelization works.